2020
DOI: 10.1109/access.2020.3028735
|View full text |Cite
|
Sign up to set email alerts
|

Fast True Random Number Generator Based on Chaotic Oscillation in Self-Feedback Weakly Coupled Superlattices

Abstract: Random numbers play a vital role in communications and cryptography. However, most existing true random number generators have difficulty in satisfying the requirements of high-speed communications due to their complexity and bulkiness, or low speed limitations due to equipment bandwidth. Then, the all-electron true random number generator was presented based on GaAs/Al 0.45 Ga 0.55 As superlattices conducted under direct current bias at room temperature, which not only possesses the characteristics of miniatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The chaotic oscillation phenomenon of SSL can be used to generate random bits at high speed and enough entropy, which has attracted considerable interest recently 33 35 . Under specific offset voltage, the SSL is an ideal non-linear dynamic system with one-dimensional multi-degree-freedom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chaotic oscillation phenomenon of SSL can be used to generate random bits at high speed and enough entropy, which has attracted considerable interest recently 33 35 . Under specific offset voltage, the SSL is an ideal non-linear dynamic system with one-dimensional multi-degree-freedom.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, Huang et al 32 proposed to use GaAs/ As material instead of GaAs/AlAs to grow semiconductor superlattice and successfully observed chaos oscillation phenomenon at room temperature experimentally. Many scholars have confirmed that the SSL is an ideal entropy source by exploring the structure of the GaAs/ As SSL and the large-amplitude chaos current oscillation generate truly random numbers 33 35 . Moreover, the high-throughput embedded system of semiconductor superlattice true random number generator (SSL-TRNG) was reported recently 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The chaotic oscillation phenomenon of SSL can be used to generate random bits at high speed and can generate enough entropy, which has attracted considerable interest recently [33][34][35] . Under specific offset voltage, the SSL is an ideal non-linear dynamic system with one-dimensional multi-degree-freedom.…”
Section: Entropy Sourcementioning
confidence: 99%
“…In 2012, Huang et al 32 proposed to use GaAs/Al 0.45 Ga 0.55 As material instead of GaAs/AlAs to grow semiconductor superlattice and successfully observed chaos oscillation phenomenon at room temperature experimentally. Many scholars have confirmed that the SSL is an ideal entropy source by exploring the structure of the GaAs/Al 0.45 Ga 0.55 As SSL and the large-amplitude chaos current oscillation generate truly random numbers [33][34][35] . Moreover, the high-throughput embedded system of semiconductor superlattice true random number generator (SSL-TRNG) was reported recently 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Then various statistical tests are performed for measuring the strength of the generator. As the entropy source thermal noise on electrical components [9,10], phase jitter in oscillators [11][12][13][14],chaos [15,[17][18][19][20], spintronic [21] or optical sources [22] can be utilized. These implementations require advanced setups that require complex instrumentation and cover a large area.…”
Section: Introductionmentioning
confidence: 99%